# X prof je bilmes ee596awinter 2013dgms lecture 4 jan

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MPE Summ HMMs and elimination - forward recursion From the last line of the elimination (when we sum out qr−1 , we see α-recursion, which is: αt+1 (j ) = αt (i)p(Qt+1 = j |Qt = i)p(xt+1 |Qt+1 = j ) (4.22) α1 (j ) = p(Q1 = j )p(¯1 |Q1 = j ) x (4.23) i and We have that α1 (Q1 = j ) = p(Q1 = j )p(¯1 |Q1 = j ) = p(¯1 , Q1 = j ), and x x α1 (q1 ) = p(¯1 , q1 ). x Prof. Jeﬀ Bilmes EE596A/Winter 2013/DGMs – Lecture 4 - Jan 23rd, 2013 page 4-30 (of 239) HMMs HMMs as GMs Other HMM queries What HMMs can do MPE Summ HMMs and elimination - forward recursion From the last line of the elimination (when we sum out qr−1 , we see α-recursion, which is: αt+1 (j ) = αt (i)p(Qt+1 = j |Qt = i)p(xt+1 |Qt+1 = j ) (4.22) α1 (j ) = p(Q1 = j )p(¯1 |Q1 = j ) x (4.23) i and We have that α1 (Q1 = j ) = p(Q1 = j )p(¯1 |Q1 = j ) = p(¯1 , Q1 = j ), and x x α1 (q1 ) = p(¯1 , q1 ). x Also, α2 (q2 ) = q1 p(q2 |q1 )p(¯2 |q2 )α(q1 ) = x x x ¯¯ x¯ q1 p(q1 , q2 , x1 , x2 ) = p(¯1 , x2 , q2 ) q1 p(q2 |q1 )p(¯2 |q2 )p(¯1 , q1 ) = In general, the forward (α) recursion has meaning αt (j ) = p(x1:t , Qt = j ) Prof. Jeﬀ Bilmes EE596A/Winter 2013/DGMs – Lecture 4 - Jan 23rd, 2013 page 4-30 (of 239) HMMs HMMs as GMs Other HMM queries What HMMs can do MPE Summ HMMs and elimination - forward recursion From the last line of the elimination (when we sum out qr−1 , we see α-recursion, which is: αt+1 (j ) = αt (i)p(Qt+1 = j |Qt = i)p(xt+1 |Qt+1 = j ) (4.22) α1 (j ) = p(Q1 = j )p(¯1 |Q1 = j ) x (4.23) i and We have that α1 (Q1 = j ) = p(Q1 = j )p(¯1 |Q1 = j ) = p(¯1 , Q1 = j ), and x x α1 (q1 ) = p(¯1 , q1 ). x Also, α2 (q2 ) = q1 p(q2 |q1 )p(¯2 |q2 )α(q1 ) = x x x ¯¯ x¯ q1 p(q1 , q2 , x1 , x2 ) = p(¯1 , x2 , q2 ) q1 p(q2 |q1 )p(¯2 |q2 )p(¯1 , q1 ) = In general, the forward (α) recursion has meaning αt (j ) = p(x1:t , Qt = j ) So α (forward) recursion is just an instance of the elimination algorithm run on the GM for the HMM graph. Prof. Jeﬀ Bilmes EE596A/Winter 2013/DGMs – Lecture 4 - Jan 23rd, 2013 page 4-30 (of 239) HMMs HMMs as GMs Other HMM queries What HMMs can do MPE Summ HMMs and elimination - backward recursion Next, consider elimination order XT , QT , XT −1 , QT −1 , . . .. T .. p(xt |qt )p(qt |qt−1 )δ (xt , xt ) ¯ xT −2 qT −1 xT −1 qT xT t=1 T −1 =... p(xT |qT )p(qT |qT −1 )δ (xT , xT ) ¯ p(xt |qt )p(qt |qt−1 )δ (xt , xt ) ¯ xT −1 qT t=1 xT T −1 = ... p(xt |qt )p(qt |qt−1 )δ (xt , xt ) p(¯T |qT )p(qT |qT −1 ) ¯ x xT −1 qT Prof. Jeﬀ Bilmes t=1 EE596A/Winter 2013/DGMs – Lecture 4 - Jan 23rd, 2013 page 4-31 (of 239) HMMs HMMs as GMs Other HMM queries What HMMs can do MPE Summ HMMs and elimination - backward recursion T −1 ... p(xt |qt )p(qt |qt−1 )δ (xt , xt ) p(¯T |qT )p(qT |qT −1 ) ¯ x xT −2 qT t=1 1 βT (qT ) T −1 = ... p(xt |qt )p(qt |qt−1 )δ (xt , xt ) ¯ qT −1 xT −1 p(¯T |qT )p(qT |qT −1 )βT (qT ) x qT t=1 βT −1 (qT −1 ) This corresponds to the β recursion βt (qt ) = βt+1 (qt+1 )p(qt...
View Full Document

## This document was uploaded on 04/05/2014.

Ask a homework question - tutors are online